The effect of catecholaminergic depletion within the prelimbic and infralimbic medial prefrontal cortex on recognition memory for recency, location, and objects - Nelson, Andrew J.D.; Cooper, Molly T.; Thur, Karen E.; Marsden, Charles A.; Cassaday, Helen J. (American Psychological Association, 2011)
There is good evidence that the medial prefrontal cortex (mPFC) is involved in different aspects of recognition memory. However, the mPFC is a heterogeneous structure, and the contribution of the prelimbic (PL) and infralimbic (IL) cortices to recognition memory has not been investigated. Similarly, the role of different neuromodulators within the mPFC in these processes is poorly understood. To this end, we tested animals with 6-hydroxydopamine (6-OHDA) lesions of the PL and IL mPFC on three tests of object recognition memory that required judgments about recency, object location, and object identity. In the recency task, lesions to both PL and IL severely impaired animals' ability to differentiate between old (earlier presented) and recently presented familiar objects. Relative to sham and PL animals, the IL lesion also disrupted performance on the object location task. However, both lesions left novel object recognition intact. These data confirm previous reports that the mPFC is not required for discriminations based on the relative familiarity of individual objects. However, these results demonstrate that catecholamines within the PL cortex are crucial for relative recency judgments and suggest a possible role for neural processing within the IL in the integration of information about object location